Cross-layer Solutions in WSN Routing: A Review - Sheethal Raj T G; Nirmala Hiremani (International Journal of Wireless Security and Networks, 2023)
WSN is a less infrastructure wireless network which is embedded with large number of Sensor Nodes (SN). Its ad-hoc manner of device distribution allows it to monitor conditions under physical and environmental scenarios. Typically, SNs in WSN are installed in a specified geographical location to monitor required information. Due to SNs’ self-configuring ability, the exploitation of target is simpler. Though, its functioning is limited with factors such as energy efficiency, processing and memory. Therefore, various research works on cross-layer design models for WSN have been proposed. In this survey, 25 research papers are reviewed and analyzed. The analyses are categorized under routing protocols/routing models, performance measures and simulation tools. The issues that need to be solved in future are analyzed and dropped out in this survey. Finally, this research enables researchers to work on finding an optimal cross-layer solution in WSN routing.
Keywords: Cross-layer optimization; Performance measures; QoS parameters and Simulation tools; WSN routing